The modification of graphene oxide and studies of the detection of norovirus DNA and RNA - Le, Duy Duc (Kansas State University, 2013)
Graphene oxide (GO) has attracted many researchers in the past years because of its unique electrical and chemical properties which showed the potential applications in many fields such as electronic materials and biology. Increasing research efforts in the biomedical field are bringing to light new discoveries in areas such as drug delivery, treatment of cancers, and biosensors, and are therefore attractive. The purpose of this work is to prepare GO and modify the surface of GO in order to achieve a new functionalized GO for biosensor applications in the future. GO was synthesized from the flake graphite by using a modified Hummer’s method to achieve higher quality and yield. The flake graphite was first exfoliated by using a microwave reactor. The exfoliated flake graphite then was oxidized by K[subscript]2S[subscript]2O[subscript]8, P[subscript]2O[subscript]5, and KMnO[subscript]4 under acidic conditions, followed by H[subscript]2O[subscript]2 to form GO. The following steps were to attach carboxylic acid and benzoic acid groups onto the surface of GO. Atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy were used to identity the modified GO and determine the sizes of the materials after a sequence of reactions. The modified GO will be used in the study of electronic sensing of biomolecules in Hua’s laboratory.
Keywords: Graphene oxide; Modification; Norovirus; DNA; RNA; Hummer’s method; Chemistry (0485)